Penerapan Maslahah Mursalah dalam Pengeolaan Zakat Profesi pada BAZNAS Kabupaten Tuban - Husnama Patih (ITB AAS INDONESIA Surakarta, 2022)
In line with the development of the era, creates more type of professions. Teacher, docter, police, journalist and pilot are renown professions. Those professions are top nomination for job seeker to gets appropriate income. However, in their salary there are right of others, as in islamic laws for kinds of proffesion on holy Quran as well as hadith. Every professions for example farmers and their farms, salesmans and their goods, herdsmans and their shepherds, has obligation to fulfill zakat base on the count. The ancient time there is nothing standard count for management profession zakat and zakat management unit. Zakat management unit is not only collect zakat but also manage and distribute zakat. The presence of baznas in every districts helps society to collect and to distribute zakat, include profession zakat. Baznas of Tuban district has collected most of ZIS funds in east java 2019 through their programs. Those programs run with take into consederation of maslahah mursalah both of collect and distribute, no exception with profession zakat.